2010
DOI: 10.1203/pdr.0b013e3181cb8e68
|View full text |Cite
|
Sign up to set email alerts
|

Apolipoprotein E4 and Sex Affect Neurobehavioral Performance in Primary School Children

Abstract: Apolipoprotein E4 (apoE4) and female sex are risk factors for developing Alzheimer's disease. It is unclear whether apoE4 contributes to behavioral function at younger ages. Standard neuropsychological assessments [intelligence quotient (IQ), attention, and executive function] and a test developed in this laboratory (Memory Island test of spatial learning and memory) were used to determine whether E4 and sex affect neuropsychological performance in healthy primary school children (age 7-10). A medical history … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
64
2

Year Published

2010
2010
2021
2021

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 63 publications
(69 citation statements)
references
References 49 publications
3
64
2
Order By: Relevance
“…Interestingly, a very recent report showed similar cognitive impairment in 3-month-old apoE4-targeted replacement mice (71). Further strengthening this hypothesis is another interesting study that shows evidences of spatial memory deficits in apoE4-positive children as young as 7 years old (72). Therefore, observing such a cognitive phenotype in young Arg-61 mice suggests that domain interaction feature of apoE4 may be sufficient to cause cognitive impairment in young apoE4 subjects in the absence of AD pathology.…”
Section: Discussionmentioning
confidence: 68%
“…Interestingly, a very recent report showed similar cognitive impairment in 3-month-old apoE4-targeted replacement mice (71). Further strengthening this hypothesis is another interesting study that shows evidences of spatial memory deficits in apoE4-positive children as young as 7 years old (72). Therefore, observing such a cognitive phenotype in young Arg-61 mice suggests that domain interaction feature of apoE4 may be sufficient to cause cognitive impairment in young apoE4 subjects in the absence of AD pathology.…”
Section: Discussionmentioning
confidence: 68%
“…Amyloid imaging and autopsy studies have demonstrated a similar topographic distribution, but with more extensive and greater Aβ plaque deposition in isocortical regions, including frontal and parietal lobes, in carriers relative to noncarriers (23,54). Thus, the less-prominent atrophy of these brain regions in ε4 carriers may be mediated through other mechanisms, perhaps related to differential response of isocortical neurons to AD pathology or even developmental influences of APOE genotype, which may relate to individual differences in cognitive performance (55,56), neuroanatomy (57), or brain function (52) at a young age. For example, several reports in young adults or children have suggested that noncarriers perform less well on measures of executive functioning and processing speed but better on tests of memory, foreshadowing the more prominent dissociation in the context of AD described here (55,56,58).…”
Section: Discussionmentioning
confidence: 94%
“…Thus, the less-prominent atrophy of these brain regions in ε4 carriers may be mediated through other mechanisms, perhaps related to differential response of isocortical neurons to AD pathology or even developmental influences of APOE genotype, which may relate to individual differences in cognitive performance (55,56), neuroanatomy (57), or brain function (52) at a young age. For example, several reports in young adults or children have suggested that noncarriers perform less well on measures of executive functioning and processing speed but better on tests of memory, foreshadowing the more prominent dissociation in the context of AD described here (55,56,58). These observations hint that APOE genotype may work in complex dissociable ways to modulate functional-anatomic brain networks subserving cognition throughout the lifespan and also the differential vulnerability of these networks to AD later in life (59).…”
Section: Discussionmentioning
confidence: 99%
“…One reason for this may be variation in the statistical power for individual studies. Whereas some studies with large sample sizes, and therefore high statistical power, found no differences (e.g., Deary et al, 2003;Jorm et al, 2007;Taylor et al, in press), other studies with small sample sizes, and therefore lower statistical power, did find APOE ɛ4-related benefits (e.g., Acevedo et al, 2010;Marchant et al, 2010;Puttonen et al, 2003;Yu et al, 2000). Type I or II errors may explain some of the variation in findings, but generally studies with small Ns tend to either over-or underestimate effect sizes, whereas investigations with large Ns estimate effect sizes more accurately.…”
Section: It Is Clear That There Are Inconsistencies In Research Findimentioning
confidence: 98%